Adverse Events During Treatment Induction With Injectable Diacetylmorphine and Hydromorphone for Opioid Use Disorder. Issue 5 (September 2019) - Oviedo-Joekes, Eugenia; Palis, Heather; Guh, Daphne; Marsh, David C.; MacDonald, Scott; Harrison, Scott; Brissette, Suzanne; Anis, Aslam H.; Schechter, Martin T.
Abstract : Objectives: The present study aims to describe a 3-day induction protocol for injectable hydromorphone (HDM) and diacetylmorphine (DAM) used in 3 Canadian studies and examine rates of opioid-related overdose and somnolence during this induction phase. Methods: The induction protocol and associated data on opioid-related overdose and somnolence are derived from 2 clinical trials and one cohort study conducted in Vancouver and Montreal (2005–2008; 2011–2014; 2014–2018). In this analysis, using the Medical Dictionary for Regulatory Activities coding system we report somnolence (ie, drowsiness, sleepiness, grogginess) and opioid overdose as adverse events. Overdoses requiring intervention with naloxone are coded as severe adverse events. Results: Data from the 3 studies provides a total of 1175 induction injections days, with 700 induction injection days for DAM, and 475 induction injection days for HDM. There were 34 related somnolence and adverse event (AE) overdoses (4.899 per 100 injection days) in DAM and 6 (1.467 per 100 days) in HDM. Four opioid overdoses requiring naloxone (0.571 per 100 injection days) were registered in DAM and 1 in HDM (0.211 per 100 injection days), all safely mitigated onsite. The first week maximum daily dose patients received were on average 433.62 mg [standard deviation (SD) = 137.92] and 223.26 mg (SD = 68.06) for DAM and HDM, respectively. Conclusions: A 3-day induction protocol allowed patients to safely reach high doses of injectable hydromorphone and diacetylmorphine in a timely manner. These findings suggest that safety is not an evidence-based barrier to the implementation of treatment with injectable hydromorphone and diacetylmorphine. Abstract : Supplemental Digital Content is available in the text